Penguatan Peran Kader Posyandu sebagai Agen Edukasi Tuberkulosis melalui Pemanfaatan Media Edukasi Berbasis Komunitas di Kelurahan Bumi - Putri, Vania Santika; Dewi, Aptika Oktaviana Trisna; Setiyawan, Bagus (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Integrated Health Service Post (Posyandu) cadres have strategic potential as spearheads in early detection and TB education at the community level. The objective of this community service activity is to increase the capacity and active role of Posyandu cadres in Bumi Village as educational agents in TB prevention and early detection efforts. The activity is carried out in three continuous stages, including the preparation and needs analysis stage, the declaration of a TB-aware village, and Posyandu cadre training on TB education and early detection. The cadre training was carried out using interactive educational media in the form of PowerPoint presentations, leaflets, videos, and checklists to increase understanding of TB epidemiology, transmission mechanisms, clinical symptoms, prevention, and referral pathways. Evaluation results show the potential for increasing cadre knowledge, the ability to screen suspects, and their confidence in providing counseling to the community. A community-based educational approach involving trained cadres and interactive media can increase community preparedness, reduce stigma, and strengthen efforts to find cases and prevent TB transmission at the village level.